Evaluación del valor nutricional de recetas típicas elaboradas con maíz común y biofortificado en el Departamento del Cauca, Colombia - Imbachí Narváez, P.C.; Gutiérrez, D.; Ortíz, D.A.; Pachón, Helena (2010)
Objective. Ten typical recipes from southwestern Colombia were evaluated at CIAT in Palmira, Colombia between 2008 and 2009. Material and Methods. The recipes were prepared in a traditional manner, using quality protein maize (QPM, with more tryptophan and lysine) or common maize (CM); each of these was either fresh kernel or dry grain, or white or yellow maize, per the recipe. The two types of maize were compared for their protein quality. Results. Tryptophan concentrations were 0.011-0.072% and 0.012-0.107% for CM and QPM, respectively. Tryptophan values for QPM recipes were greater than or equal to those for CM recipes. Soluble protein ranged from 2.359-14.783 g/kg for CM and 3.339-16.839 g/kg for QPM. Except for one recipe, soluble protein in QPM recipes was greater or equal to that of CM recipes. In vitro protein digestibility was 75-84% for recipes prepared with both maize types. Only four recipes had a statistically significant difference between QPM and CM with regard to digestibility. Conclusions. Most recipes prepared with QPM had a higher protein quality than those prepared with CM.